Earthquake-induced permanent deformations of tailings dams - Pascual, Jerome G.; Rabonza, Maricar L.; Zarco, Mark Albert H.; Azul, Kristian M. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Studies about earthquake-induced permanent deformation tailings dams in the Philippines appear in almost trifling volumes. This paper reports the permanent deformations of 9 dams located in seismically active locations in the Philippines namely (I) Masbate Gold Tailings Storage Facility (TSF) in Masbate and (2) Rapu-Rapu TSF which are calculated using three different established methods - Newmark Sliding Block Analysis, Makdisi-Seed Analysis and the Elastic-Plastic Stress Redistribution (EPSR) Method coupled with FEM Nonlinear Dynamic Analysis. By following a deterministic approach, Wells and Coppersmith Method is applied to select a main input earthquake with critical parameters (magnitude and PGA). For the sensitivity analyses, earthquakes with varying magnitudes and predominant frequencies (calculated using Fast Fourier Transform) were adopted in the deformationanalyses as well. Newmark Sliding Block Analysis is found to produce overestimated deformations for soils with visco-plastic response and underestin1ated results for soils with drastic shear loss. Makdisi-Seed exhibited relatively closer deformations to EPSR (at most 2%). Ultimately, EPSR, though tedious, is believed to be the most effective method if sophisticated results are desired. The sensitivity analyses proved that earthquakes with predominant frequencies corresponding to the natural frequency of the dam may produce larger deformations.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Tailings dams -- Philippines; Dams -- Earthquake effects